1994
DOI: 10.1111/j.1528-1157.1994.tb02459.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate: Preclinical Evaluation of a Structurally Novel Anticonvulsant

Abstract: Topiramate [TPM, 2,3:4,5-bis-O-(1-methylethylidene)-beta-D-fructopyranose sulfamate] (RWJ-17021-000, formerly McN-4853) is a structurally novel antiepileptic drug (AED). The preclinical anticonvulsant profile suggests that TPM acts primarily by blocking the spread of seizures. TPM was highly effective in the maximal electroshock (MES) seizure test in rats and mice. Activity was evident < or = 0.5 h after oral administration and lasted at least 16 h. The ED50 values 4 h after oral dosing were 13.5 and 40.9 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
219
1
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(230 citation statements)
references
References 23 publications
5
219
1
5
Order By: Relevance
“…392,393 The action of topiramate on carbonic anhydrase has been assumed not to contribute to its clinical efficacy, because cross-tolerance to the anticonvulsant activity of topiramate does not occur with acetazolamide in mice. 394 However, a recent study finds closely comparable potency for acetazolamide and the two AEDs against cytosolic carbonic anydrase isozyme II and mitochondrial carbonic anhydrase isozyme V. 395 Carbonic anhydrase is a zinc-containing enzyme that is inhibited by interaction of sulfonamide or sulfamate compounds with the Zn(II) ion and specific residues of the protein. X-ray crystallography of human carbonic anhydrase II with zonisamide demonstrates a classical interaction with the protein that is characteristic of sulfonamides, as is zonisamide.…”
Section: Carbonic Anhydrasementioning
confidence: 99%
“…392,393 The action of topiramate on carbonic anhydrase has been assumed not to contribute to its clinical efficacy, because cross-tolerance to the anticonvulsant activity of topiramate does not occur with acetazolamide in mice. 394 However, a recent study finds closely comparable potency for acetazolamide and the two AEDs against cytosolic carbonic anydrase isozyme II and mitochondrial carbonic anhydrase isozyme V. 395 Carbonic anhydrase is a zinc-containing enzyme that is inhibited by interaction of sulfonamide or sulfamate compounds with the Zn(II) ion and specific residues of the protein. X-ray crystallography of human carbonic anhydrase II with zonisamide demonstrates a classical interaction with the protein that is characteristic of sulfonamides, as is zonisamide.…”
Section: Carbonic Anhydrasementioning
confidence: 99%
“…Topiramate (TPM), a promising new antiepileptic agent (AED) derived from the monosaccharide Dfructose, is a structurally novel compound (1). In animal models, TPM has exhibited a broad spectrum of anticonvulsant activity similar to that of carbamazepine (CBZ) and phenytoin (PHT).…”
mentioning
confidence: 99%
“…In animal models, TPM has exhibited a broad spectrum of anticonvulsant activity similar to that of carbamazepine (CBZ) and phenytoin (PHT). Its activity appears to be attributable to a block of seizure spread rather than to an increase of seizure threshold (1). Clinical trials to date have demonstrated that TPM greatly enhances seizure control when used as adjunctive treatment in adults with partialonset seizures (2).…”
mentioning
confidence: 99%
“…TPM appears to have multiple antiepileptic actions in rodent models (13)(14)(15)(16)(17). In vitro studies show enhanced ␥-aminobutyric acid subtype A (GABA A )-receptor mediated chloride flux.…”
mentioning
confidence: 99%